1983
DOI: 10.1111/j.1600-0560.1983.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine spiradenoma: clinical and pathologic study of 49 tumors

Abstract: A clinical and pathologic study of 49 eccrine spiradenomas occurring in 46 patients is presented. The study showed that pain and/or tenderness are not such characteristic clinical features of this tumor as has previously been suggested; either or both were present in only 23% of the 35 patients with well-documented clinical histories. Some pathologic features, not previously documented in this tumor, were seen and included: cylindromatous foci, aggregates of stromal clear cells, clear cells lining ducts and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 18 publications
(31 reference statements)
1
71
0
1
Order By: Relevance
“…Clear cell change is a frequent incidental feature in a range of cutaneous adnexal tumors. 16,[17][18][19][20][21][22][23][24][25][26][27][28] Clear cell change has been noted in both spiradenoma and spiradenocarcinoma. 23,29 Among the tumors in our series, clear cell areas varied morphologically and immunohistochemically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear cell change is a frequent incidental feature in a range of cutaneous adnexal tumors. 16,[17][18][19][20][21][22][23][24][25][26][27][28] Clear cell change has been noted in both spiradenoma and spiradenocarcinoma. 23,29 Among the tumors in our series, clear cell areas varied morphologically and immunohistochemically.…”
Section: Discussionmentioning
confidence: 99%
“…16,[17][18][19][20][21][22][23][24][25][26][27][28] Clear cell change has been noted in both spiradenoma and spiradenocarcinoma. 23,29 Among the tumors in our series, clear cell areas varied morphologically and immunohistochemically. In case 2, which had an appearance reminiscent of epithelialmyoepithelial carcinoma of the salivary glands or adenomyoepitheliomatous differentiation in some breast lesions, 30 the clear cells were myoepithelial in nature.…”
Section: Discussionmentioning
confidence: 99%
“…A third of eccrine spiradenomas occur in the head and neck, a third on the trunk, a fifth on the extremities and the remainder in a variety of sites. 18 Eccrine spiradenomas are well known for being painful and are one of nine painful cutaneous tumors: leiomyoma, neuroma, dermatofibroma, angiolipoma, neurilemmoma, endometrioma, glomus tumor and granular cell tumor. 19 The etiology of pain in eccrine spiradenoma differs from that of adenoid cystic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Eccrine spiradenoma shows many characteristic histopathological features [4,8,17]. Our specimen also displayed these distinctive histological features with two types of cells in the tumor nodule.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, Mambo [8] reported that pain or tenderness was present much less frequently (only 23%) in his clinical and histopathological review of 49 cases of eccrine spiradenoma. …”
Section: Discussionmentioning
confidence: 99%